(untitled) (Світ фінансів, 2017)
Ткач К. М. Прагматизм надання та розподілу інвестиційних субвенцій. Обґрунтовано необхідність реформування механізму розподілу інвестиційних субвенцій з державного бюджету між місцевими бюджетами на основі формалізованого методу. Запропоновано конкретні пропозиції в цьому напрямку з урахуванням соціально-економічного розвитку територій. Tkach K. The pragmatism of the provision and the allocation of the investment subventions. The necessity of reforming the mechanism of allocation of the investment subventions from the State budget between local budgets, which is based on formalized method, is substantiated. Some specific proposals are suggested in this direction with the consideration of the social and economic development of the territories.